Impact of Body Mass Index (BMI) on Echocardiography - Kaleem Ullah Toori, Kaleem Ullah Toori; Yasser Jalil Khan, Yasser Jalil Khan (Journal of Rawalpindi Medical College, 2007)
Background: To determine the demographic characteristics of patients in various BMI groups and the impact of individual BMI group on the utility of transthoracic echocardiography . Methods: This prospective observational study was conducted at KRL Hospital, Islamabad from Dec 1, 2006 to Apr 30, 2007. 224 patients, 52% males with mean age 51.4 years (SD±17.23) referred for trans-thoracic echocardiography were studied. All patients had their BMI calculated and test indication, details of echocardiography findings and final conclusion recorded. Results: Forty nine percent of the study population was overweight and obese with female predominance (59%). The normal and underweight people were significantly younger in age (p<0.001) and were mainly referred for assessment of heart murmur. The overweight and obese were referred mainly for assessment of LV function and had significantly high number of poor technical quality echo images (p<0.001). In total 54% of the echocardiograms were normal. Relatively more normal results were obtained in overweight & obese (59%) as compared to normal & underweight people (50%). Obesity was more prevalent in female gender. Both the subgroups (normal/underweight & overweight/obese) used the echocardiography service equally. Conclusion: The high number of normal echocardiograms in overweight & obese people who were mainly referred for assessment of LV function appears to be an inappropriate burden on echocardiography service. Assessment of heart murmur in normal and underweight population is probably due to high prevalence of rheumatic fever in our country.